SAT0097 Success in osteoarthritis (oa) trial: celecoxib significantly reduces the risk of upper gastrointestinal (ugi) hospitalizations compared to diclofenac and naproxen in 13, 274 randomised patients with oa. (1st June 2001) - Goldstein, J; Eisen, G; Bensen, W; Agrawal, N; Singh, G; Pavelka, K; Burke, TA; Chancellor, JVM; Pettitt, AD; Wilson, AM; Fort, J
Abstract : Background: NSAIDs increase the risk of serious GI hospitalizations, with studies demonstrating 5–7x increases in risk (1%?1.5% NSAID vs 0.1%-0.2% background rates). Additionally, GI-related hospitalizations impose higher cost on payers. Objectives: To compare the incidence of upper GI (UGI) hospitalizations in OA patients exposed to celecoxib, a COX-2 specific inhibitor, or conventional NSAIDs (diclofenac or naproxen). Methods: SUCCESS-1 in OA was a 12-week, multinational, double-blind, randomised trial in 13, 274 patients, designed to reflect standard clinical practice. 6547 patients from Europe and Africa; 2756 from North America; 2889 from Latin America and 1082 from Australasia were enrolled. Patients were treated with celecoxib (200 mg/d [n = 4421] or 400 mg/d [n = 4429]) or conventional NSAIDs (naproxen 1000 mg/d [n = 914] or diclofenac 100 mg/d [n = 3510]). An independent Gastrointestinal Events Committee (GEC) categorised potential clinically significant UGI events in a blinded fashion as UGI ulcer complications (perforations, gastric outlet obstruction, bleeding) or symptomatic UGI ulcerations. UGI hospitalizations are reported as GI body system code events, investigator-determined potential UGI events, and GEC-confirmed ulcers/ulcer complications. Results: Conclusion: UGI hospitalisation rates were 2–4x lower, and less UGI-related healthcare resources were utilised for celecoxib- vs NSAID-treated patients. The incidence of serious clinical UGI safety endpoints was significantly lower in the celecoxib-treated patients. Sponsored by Pharmacia Corporation and Pfizer, Inc.